Peran Leadership Dalam Mengelola Sumber Daya Manusia Yang Berkualitas - Mukaromah Syakoer (J-CEKI : Jurnal Cendekia Ilmiah, 2023)
Human resources are one of the crucial factors that can determine the growth and success of an organization. The quality of human resources is a component that needs careful attention in an organization and is closely related to the role, position, and function of leadership in the organization. Leadership with a focus on principles and professional values easily guides an organization to grow and develop in line with its vision and mission. Additionally, leadership serves as a vital instrument in an organization. The aim of this research is to understand the role of leadership in managing high-quality human resources (HR). The research methodology employed is a literature review using Google Scholar as tools. The research findings state that leadership plays a crucial role in creating positive changes in building high-quality HR, enhancing the quality of public services, and overall organizational performance.